Validity and Redescription of Profundulus balsanus Ahl, 1935 (Cyprinodontiformes: Profundulidae) - Jamangapé O, José A.; Velázquez-Velázquez, Ernesto; Martínez-Ramirez, Emilio; Anzueto-Calvo, Manuel J.; Gomez, Eyda L.; Dominguez-Cisneros, Sara E.; Mcmahan, Caleb D.; Matamoros, Wilfredo A. (Zootaxa, 2016)
Profundulus balsanus was described by Ahl in 1935 and later placed in synonymy with P. punctatus. Recent molecular studies have demonstrated that specimens identified as P. balsanus belong to a distinct taxon. Herein we used a combination of morphometric, meristic, coloration and osteological data in order to demonstrate the distinctiveness of P. balsanus. Additionally, we used molecular data to reconstruct a phylogeny to place P. balsanus in a systematic context. Profundulus balsanus belongs to the punctatus clade within the genus Profundulus. It can be distinguished from P. oaxacae based on scale count in the lateral line and from P. punctatus based on differences in coloration in the anal fin. We provide a taxonomic key to all Mexican species of Profundulus.